A semiótica da cultura nas abordagens socioculturais da organização do conhecimento: uma análise teórico-conceitual - Farias, Mona Cleide Quirino da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Semiotics of Culture is a field of study whose investigations are to analysis of language, specifically the language of culture. The Semiotics of Culture deals with sign systems of culture and recognizes that culture is generating element of several texts, which leads us to understand that the context is presented as decisive for understanding the development of signs of culture, as well as the organization processes and representation of knowledge. The conception of language and culture are elements that boost the discussions in the Semiotics of Culture. It was on this premise that we seek the reflection on the cultural diversity and linguistic diversity that exists in many contexts of the culture. The question that guided the analysis of this study was to know what the theoretical and conceptual relationships between the Semiotics of Culture and socio cultural approaches to Knowledge Organization. Thereunto, we aim to draw an analysis of theoretical and conceptual relationships between the Semiotics of Culture and Knowledge Organization, more precisely to socio cultural approaches highlighting the authors: Begthol, García Gutiérrez and Hudon. The methodological procedures were based on a qualitative and exploratory character approach. The research corpus gathers materials from the field of Knowledge Organization and the Semiotics of Culture. The analysis method used was a Content Analysis that contributed to the analysis of the concepts of the two fields of study in order to reach the objectives. Thereby, the analyses were performed on the concepts that feature the socio cultural approaches and conceptions of Semiotics of Culture. With the analysis of the texts we present the dialogue between the Semiotics of Culture and socio cultural approaches. Thus, we consider that the objectives of this research were achieved. So, we believe that the Semiotics of Culture can contribute to the Knowledge Organization based on an analysis...

A Semiótica da Cultura é um campo de estudo cujas investigações estão para análise da linguagem, mais precisamente das linguagens da cultura. A Semiótica da Cultura trata dos sistemas de signos da cultura e reconhece que a cultura é elemento gerador de diversos textos, o que nos leva a entender que o contexto se apresenta como determinante para compreender o desenvolvimento dos signos da cultura, assim como para os processos de organização e representação do conhecimento. A concepção de linguagem e cultura são elementos que impulsionam as discussões na Semiótica da Cultura. Foi com base nesta premissa que buscamos a reflexão em torno da diversidade cultural e da diversidade linguística existente em diversos contextos da cultura. A questão que norteou a análise deste trabalho foi saber quais as relações teóricas e conceituais entre a Semiótica da Cultura e as abordagens socioculturais da Organização do Conhecimento. Para tanto, objetivamos traçar uma análise sobre relações teórico-conceituais entre a Semiótica da Cultura e a Organização do Conhecimento, mais precisamente às abordagens socioculturais com destaque aos autores: Begthol, García Gutiérrez e Hudon. Os procedimentos metodológicos tomaram como base uma abordagem qualitativa e de caráter exploratória. O corpus da pesquisa reúne materiais do campo da Organização do Conhecimento e da Semiótica da Cultura. O método de análise utilizado foi a Análise de Conteúdo que contribuiu na análise dos conceitos dos dois campos de estudo, tendo em vista o alcance dos objetivos. Desse modo, realizaram-se as análises sobre os conceitos que caracterizam as abordagens socioculturais e as concepções da Semiótica da Cultura. Com a análise feita sobre os textos apresentamos o diálogo entre a Semiótica da Cultura e as abordagens socioculturais. Assim, consideramos que os objetivos desta pesquisa foram alcançados. Portanto, entendemos que a Semiótica...
Keywords: Cultura - Semiótica; Pluralismo cultural; Linguagem e cultura; Linguística; Análise de conteúdo (Comunicação); Language and culture